Relationship of Leadership Style to Completeness of Filling in The Early Nursing Assessment in Hospital - Prestasianita Putri; Alfid Tri Afandi; Dian Wahyu Fajaryanti (KHD-Production, 2021)
Initial assessment has a very important role in determining the right nursing diagnosis, planning nursing actions, implementing actions and assessing/evaluating nursing. Initial assessment data is incomplete, precise and accurate resulting in nursing care will not achieve optimal goals. This study aims to determine the relationship between leadership style and the completeness of filling out the initial inpatient nursing assessment at Bina Sehat Hospital Jember. The research design is descriptive correlation with cross sectional,data analysis chi square, total population of all inpatient nurses, with a total sample of 79 nurses (total sampling). The results showed that there was no relationship between leadership style and the completeness of filling out the initial inpatient nursing assessment at Bina Sehat Hospital Jember (p=0.772). The majority of leadership style assessments are participatory (82.3%), where from 79 nurse respondents, 47 nurses are majority with a working period of > 5 years (59.5%), while in terms of education the majority of D3 nursing graduates are 40 nurses (50.6 %). Hospital agencies can maintain a participatory leadership style carried out by the head of the inpatient room, to be able to work together in decision making that can increase the creativity and work responsibilities of nurses, one of which is the completeness of nursing documentation, so that quality nursing services will be created.